High-resolution quantification of root dynamics in split-nutrient rhizoslides reveals rapid and strong proliferation of maize roots in response to local high nitrogen - in 't Zandt, Dina (Journal of experimental botany, 2015)
© The Author 2015. Published by Oxford University Press on behalf of the Society for Experimental Biology.